Public–Private Partnerships to Advance Regional Ocean-Observing Capabilities: A Saildrone and NOAA-PMEL Case Study and Future Considerations to Expand to Global Scale Observing - Meinig, Christian; Burger, Eugene F.; Cohen, Nora; Cokelet, Edward D.; Cronin, Meghan F.; Cross, Jessica N.; de Halleux, Sebastien; Jenkins, Richard; Jessup, Andrew T.; Mordy, Calvin W.; Lawrence-Slavas, Noah; Sutton, Adrienne J.; et al. (Frontiers in Marine Science, 2019)
Partnership between the private sector and the ocean observing community brings exciting opportunities to address observing challenges through leveraging the unique strengths of each sector. Here, we discuss a case study of a successful relationship between the National Oceanic and Atmospheric Administration (NOAA) Pacific Marine Environmental Laboratory (PMEL) and Saildrone to instrument an Unmanned Surface Vehicle (USV) in order to serve shared goals. This case study demonstrates that a private company working with a federal laboratory has provided innovative ocean observing solutions deployed at regional scale in only a few years, and we project that this model will be sustainable over the long-term. An alignment of long-term goals with practical deliverables during the development process and integrating group cultures were key to success. To date, this effort has expanded NOAA’s interdisciplinary observing capabilities, improved public access to ocean data, and paved the way for a growing range of USV applications in every ocean. By emphasizing shared needs, complementary strengths, and a clear vision for a sustainable future observing system, we believe that this case study can serve as a blueprint for public and private partners who wish to improve observational capacity. We recommend that the international scientific community continue to foster collaborations between the private sector and regional ocean observing networks. This effort could include regional workshops that build community confidence through independent oversight of data quality. We also recommend that an international framework should be created to organize public and private partners in the atmospheric and oceanographic fields. This body would coordinate development of observational technologies that adhere to best practices and standards for sensor integration, verification, data quality control and delivery, and provide guidance for unmanned vehicle providers. Last, we also recommend building bridges between the private sector, ocean observing community, and the operational forecast community to consider the future of this new private sector, with goals to determine targeted ocean observing needs; assess the appropriateness of USVs as science platforms, sensors, and data format standards; and establish usage and data quality control and distribution protocols for ocean observing and operational forecasting.